Aggressive Behaviour of Metastatic Melanoma in a Patient with Neurofibromatosis Type 1 - Robert W. Foley; Robert M. Maweni; Aurelie Fabre; David G. Healy (Case Reports in Surgery)
Malignant melanoma is a common skin neoplasm bearing poor prognosis when presenting with metastases. Rarely melanoma metastases present without an identifiable primary cutaneous lesion despite exhaustive workup. We describe the case of a solitary lung metastasis in a patient with neurofibromatosis type 1 without an identifiable primary tumour. The rapid progression of this malignant neoplasm that led to the patient’s death within 1 year is described.